Root Patterning: Tuning SHORT ROOT Function Creates Diversity in Form - Hernández-Coronado, Marcela; Ortiz-Ramírez, Carlos (Frontiers in Plant Science, 2021)
Roots have a fundamental role in plant growth and adaptation to different environments. Diversity in root morphology and architecture enables plants to acquire water and nutrients in contrasting substrate conditions, resist biotic and abiotic stress, and develop symbiotic associations. At its most fundamental level, morphology is determined by discrete changes in tissue patterning. Differences in the number and arrangement of the cell layers in the root can change tissue structure, as well as root length and grith, affecting important productivity traits. Therefore, understanding the molecular mechanisms controlling variation in developmental patterning is an important goal in biology. The ground tissue (GT) system is an ideal model to study the genetic basis of morphological diversity because it displays great interspecific variability in cell layer number. In addition, the genetic circuit controlling GT patterning in Arabidopsis thaliana has been well described, although little is known about species with more complex root anatomies. In this review we will describe the Arabidopsis model for root radial patterning and present recent progress in elucidating the genetic circuitry controlling GT patterning in monocots and the legume Medicago truncatula (Mt), species that develop roots with more complex anatomies and multilayered cortex.